Smoking Cessation in Indigenous Populations of Australia, New Zealand, Canada, and the United States: Elements of Effective Interventions - Digiacomo, Michelle; Davidson, Patricia; Abbott, P.; Davison, J.; Moore, L.; Thompson, S. (Molecular Diversity Preservation International (MDPI), 2011)
Indigenous people throughout the world suffer a higher burden of disease than their non-indigenous counterparts contributing to disproportionate rates of disability. A significant proportion of this disability can be attributed to the adverse effects of smoking. In this paper, we aimed to identify and discuss the key elements of individual-level smoking cessation interventions in indigenous people worldwide. An integrative review of published peer-reviewed literature was conducted. Literature on smoking cessation interventions in indigenous people was identified via search of electronic databases. Documents were selected for review if they were published in a peer-reviewed journal, written in English, published from 1990–2010, and documented an individual-level intervention to assist indigenous people to quit smoking. Studies that met inclusion criteria were limited to Australia, New Zealand, Canada, and the USA, despite seeking representation from other indigenous populations. Few interventions tailored for indigenous populations were identified and the level of detail included in evaluation reports was variable. Features associated with successful interventions were integrated, flexible, community-based approaches that addressed known barriers and facilitators to quitting smoking. More tailored and targeted approaches to smoking cessation interventions for indigenous populations are required. The complexity of achieving smoking cessation is underscored as is the need to collaboratively develop interventions that are acceptable and appropriate to local populations.